Impact of Metformin Use on Survival in Patients Undergoing Liver Resection for Colorectal Cancer Metastases. Issue 11 (November 2021) - Kaltenmeier, Christof; Morocco, Brittany; Yazdani, Hamza; Reitz, Katherine; Meyer, Kelley; Molinari, Michele; Geller, David; Tohme, Samer
Introduction: Resection of colorectal liver metastases provides the best chance for survival in patients with Stage IV colorectal cancer; however, hepatic recurrence is frequent and the main cause of death. Multiple epidemiological studies have documented an association between metformin and anti-neoplastic effects in a variety of cancers. Given the vast literature, we evaluated the incidence on recurrence and survival of patients on metformin who undergo surgery for colorectal liver metastasis (CRLM). Methods: We selected 270 consecutive patients with known CRLM who underwent hepatic metastases resection at our institution between January 1st 2012 and December 31st 2019. Patients were divided based on their use of metformin (n = 62) or no metformin (n = 208). Adjusted analysis of recurrence-free (RFS) and overall survival (OS) was performed. Results: Patients on metformin had significantly longer RFS (HR: .44, 95% CI: .26-.75, P < .002; Median RFS: 49 months vs 33 months) and OS (HR .60, 95% CI .31-.97, P < .048, Median OS: 72 months vs 60 months). Additional factors associated with shorter RFS on univariate analysis included the following: CEA > 200 ng/ml (HR: 2.23, 95% CI 1.21-4.03, P < .010), positive liver margin (HR: 3.70, 95% CI 2.27-6.03, P < .001), and >1 tumor (HR: 1.98, 95% CI 1.26-3.09, P < .003). Liver margin remained a significant factor for predicting shorter OS (HR: 4.99, 95% CI 2.49-10.0, P < .001). Conclusion: In this study, we found that patients with CRLM on metformin have prolonged RFS and OS postliver resection. Further prospective randomized trials need to be carried out to evaluate the anti-neoplastic effect of metformin in diabetic and non-diabetic cancer patients.